Efficiency Enhancement of Flexible Dye Sensitized Solar Cell Using TiO2 Nanotube/ZnS Nanoparticles Photoanode - Muhammed, Ghaida Salman; Abdullah, Manal Medhat; Ali Al-Sammarraie, Abdulkareem Mohammed (Asian Journal of Chemistry, 2018)
A composite material, TiO2 nanotube arrays/ZnS nanoparticles (TNT/ZnS NPs) was assembled by deposition of ZnS nanoparticles onto anodized TiO2 nanotube by sequential chemical bath deposition method. The tube-based photoanodes are crystallized at 550 ºC prior to solar cell construction. The effect of annealing of TiO2 nanotube films at 550 ºC and pH values (7.5, 8.5 9.5) of prepared ZnS nanoparticles on the photovoltaic performance of flexible solar cells is studied. The characteristics of the flexible dye-sensitized solar cell were examined using a polyaniline as a counter electrode and KI/I2 as an electrolyte. Ruthenium dye (N719) was used as an active layer. The characterizations of the films were also accomplished by using atomic force microscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffractometry and FTIR. The flexible dye-sensitized solar cells of TNT/ZnS nanoparticles photoanode achieved a power conversion efficiency of 0.75 % under 80 mW/cm2 illuminations, which is higher than that of bare TiO2 nanotube photoanode (0.3 %).